Nanostructured Graphene Surfaces Promote Different Stages of Bone Cell Differentiation - Borghi, F. F.; Bean, P. A.; Evans, M. D. M.; Laan, T. van der; Kumar, S.; Ostrikov, K. (Nano-Micro Letters, 2018)
Nanostructured graphene films were used as platforms for the differentiation of Saos-2 cells into bone-like cells. The films were grown using the plasma-enhanced chemical vapor deposition method, which allowed the production of both vertically and horizontally aligned carbon nanowalls (CNWs). Modifications of the technique allowed control of the density of the CNWs and their orientation after the transfer process. The influence of two different topographies on cell attachment, proliferation, and differentiation was investigated. First, the transferred graphene surfaces were shown to be noncytotoxic and were able to support cell adhesion and growth for over 7 days. Second, early cell differentiation (identified by cellular alkaline phosphatase release) was found to be enhanced on the horizontally aligned CNW surfaces, whereas mineralization (identified by cellular calcium production), a later stage of bone cell differentiation, was stimulated by the presence of the vertical CNWs on the surfaces. These results show that the graphene coatings, grown using the presented method, are biocompatible. And their topographies have an impact on cell behavior, which can be useful in tissue engineering applications. Highlights: 1 Horizontally and vertically oriented carbon nanowalls (CNWs) have diverse influences on cell behavior. 2 The graphene-based topographies are nontoxic and support cell adhesion and growth. 3 Early cell differentiation was observed on the hybrid graphene layer surfaces. Later cell differentiation was stimulated by the CNW films. 4 The synergy between the CNWs and differentiation medium provides enhanced mineralization.